Trends in Mathematics and Computational Intelligence - Cornejo, María Eugenia; Kóczy, László T.; Medina, Jesús; De Barros Ruano, Antonio Eduardo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents appealing contributions on computational intelligence and mathematics, connecting both areas and offering solutions to a number of interesting, real-world problems. Such problems often require novel solutions, as complexity exceeds the tractable size. At the same time, the need for good-quality realistic solutions results in models and algorithms with a good balance of resource intensiveness and model quality (accuracy). Many areas of knowledge call for hybrid solutions that combine traditional mathematical techniques and computational intelligence based on subsymbolic knowledge representation. Important research topics are focused on developing the interaction between computational intelligence and mathematics, in order to address various challenges of the current technological age. Written by influential, leading researchers, this book discusses the latest trends in hybridising mathematics and computational intelligence.
Chapter 1. Application of the Flower Pollination Algorithm in the Analysis of Micro-CT Scans (Piotr Kowalski) -- Chapter 2. Enhancing the analysis of video time series by means of a multi-agent architecture (Luis Rodriguez-Benitez) -- Chapter 3. On the Antecedent Sets for Fuzzy Classiﬁcation of Colorectal Polyps with Stabilized KH Interpolation (Szilvia Nagy) -- Chapter 4. How to predict consistently? (Evgenii Vityaev) -- Chapter 5. Symbolic Unfolding of Multi-adjoint Logic Programs (Gines Moreno) etc.
Keywords: Computational intelligence; Artificial intelligence; Mathematics -- Data processing; Computational Intelligence; Artificial Intelligence; Computational Mathematics and Numerical Analysis